Evaluation of heavy metals content in dietary supplements in Lebanon - Korfali, Samira Ibrahim (2013)
Background: The consumption of dietary supplements is widely spread and on the rise. These dietary supplements are generally used without prescriptions, proper counseling or any awareness of their health risk. The current study aimed at analyzing the metals in 33 samples of imported dietary supplements highly consumed by the Lebanese population, using 3 different techniques, to ensure the safety and increase the awareness of the citizen to benefit from these dietary supplements. Results: Some samples had levels of metals above their maximum allowable levels (Fe: 24%, Zn: 33%, Mn: 27%, Se: 15%, Mo: 12% of samples), but did not pose any health risk because they were below permitted daily exposure limit and recommended daily allowance except for Fe in 6% of the samples. On the other hand, 34% of the samples had Cu levels above allowable limit where 18% of them were above their permitted daily exposure and recommended daily allowance. In contrast, all samples had concentration of Cr, Hg, and Pb below allowable limits and daily exposure. Whereas, 30% of analyzed samples had levels of Cd above allowable levels, and were statistically correlated with Ca, and Zn essential minerals. Similarly 62% of the samples had levels of As above allowable limits and As levels were associated with Fe and Mn essential minerals. Conclusion: Dietary supplements consumed as essential nutrients for their Ca, Zn, Fe and Mn content should be monitored for toxic metal levels due to their natural geochemical association with these essential metals to provide citizens the safe allowable amounts.